(untitled) - Billings, Henry (Singapore, 2005)
This “Adventures in reading – Intermediate” is the third in a series of three books promoting reading comprehension and vocabulary building skills for academic and social success. The structure of this textbook adapts the methods such as: adventure-based reading passages, pictures dictionary approach to vocabulary building, critical reading skills, standardized tests formats, cooperative learning tasks with graphic organizers and internet search activities.
Keywords: English language,Ngôn ngữ tiếng Anh; Reading,Đọc hiểu